Why will it never be known if convalescent plasma is effective for COVID-19 (2020)
High expectations have been set around convalescent plasma (CP) for the treatment of COVID-19. However, none of the randomized controlled trials (RCTs) conducted so far have reached their primary endpoints. Herein we report that RCTs of CP disclose a high methodological variability in inclusion criteria, outcomes, appropriate selection of donors, dosage, concentration of neutralizing antibodies and times of transfusion. Therefore, at this time there is insufficient evidence to recommend for or against the use of CP as a treatment for COVID-19.